Orality and African American Adult Education: The Art of the Spoken Word and Hip Hop - Lisa R. Merriweather Hunn; Kevin Britton (Adult Education Research Conference, 2008)
Hip Hop and The Spoken Word are popular art forms within the younger generations of the African American community. Though the listeners of these art forms recognize their educational potential, adult educators have not. This paper highlights the value of Hip Hop and The Spoken Word for informal learning.
Keywords: hip hop; spoken word; African American; informal learning